Economic models of policy-making in interdependent economies: An alternative view on competition among policies - Stefan Sinn (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1989)
This paper presents an alternative view on the appropriateness of international policy coordination. Policy-makers compete for internationally mobile capital by offering club goods which are used as input factors by firms. A country is attractive for internationally mobile capital if the price for investing there (tax rate on capital) and the quality of the club goods offered lead to higher profits than elsewhere. Because there are no spill-overs from national policy- making, policy coordination offers no gains to the benevolent politician. If policy-makers are of the Leviathantype, international policy coordination offers the chance to escape restraints that the exit mechanism of capital flight imposes upon this behaviour. Evidence on inflation and money stock trends before and after the collapse of the Bretton Woods-System serves to illustrate some of the theoretical concepts.
Keywords: 330; Internationale wirtschaftspolitische Koordination; Theorie